Sleep disturbances may influence lifestyle behaviours in women with self-reported polycystic ovary syndrome. Issue 9 (14th May 2022) - Bennett, Christie J.; Mansfield, Darren R.; Mo, Lin; Joham, Anju E.; Cain, Sean W.; Blumfield, Michelle L.; Hodge, Allison M.; Moran, Lisa J.
Abstract: Polycystic ovary syndrome (PCOS) is associated with a higher prevalence of sleep disturbances and obesity. Treatment of PCOS includes modifying lifestyle behaviours associated with weight management. However, poor sleep in the non-PCOS population has been associated with poorer lifestyle behaviours. The aim was to investigate whether sleep disturbance confounds or modifies the association between lifestyle factors and PCOS. This was a cross-sectional analysis from the Australian Longitudinal Study on Women's Health cohort aged 31–36 years in 2009 were analysed ( n 6067, 464 PCOS, 5603 non-PCOS). Self-reported data were collected on PCOS, anthropometry, validated modified version of the Active Australia Physical Activity survey, validated FFQ and sleep disturbances through latent class analysis. Women with PCOS had greater adverse sleep symptoms including severe tiredness ( P = 0·001), difficulty sleeping ( P < 0·001) and restless sleep ( P < 0·001), compared with women without PCOS. Women with PCOS also had higher energy consumption (6911 (sd 2453) v . 6654 (sd 2215) kJ, P = 0·017), fibre intake (19·8 (sd 7·8) v . 18·9 (sd 6·9) g, P = 0·012) and diet quality (dietary guidelines index (DGI)) (88·1 (sd 11·6) v . 86·7 (sd 11·1), P = 0·008), lower glycaemic index (50·2 (sd 4·0) v . 50·7 (sd 3·9), P = 0·021) and increased sedentary behaviour (6·3 (sd 2·8) v . 5·9 (sd 2·8) h, P = 0·009). There was a significant interaction between PCOS and sleep disturbances for DGI ( P = 0·035), therefore only for women who had adequate sleep was PCOS associated with a higher DGI. For women with poorer sleep, there was no association between PCOS and DGI. The association between PCOS and improved diet quality may only be maintained if women can obtain enough good quality sleep.